تطبيق التقويم تطبيق التقويم تعلم اللغة العربية في منهج مرديكا في المدرسة العالية الحكومية 4 جاكرتا الجنوبية: تطبيق التقويم تعلم اللغة العربية في منهج مرديكا في المدرسة العالية الحكومية 4 جاكرتا الجنوبية - Zahra Maulida Fitri; Ahmad Rizki Nugrahawan (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
This study serves to see the steps in evaluating Arabic language learning based on the independent curriculum in MAN 4 South Jakarta which has implemented the Merdeka curriculum in the 2022-2023 teaching period. . The approach that researchers use is a case study with descriptive qualitative analysis. The result of this study is that the implementation of the evaluation of Arabic language learning at MAN 4 Jakarta begins by formulating a learning evaluation that looks at, TP / ATP and CP. The evaluation begins with carrying out a Formative Assessment where students are asked to do practice questions in the form of homework at the end of learning and there is a repetition of the material. Diagnostic assessment is carried out by processing speaking and writing skills through whatsapp social media and summative assessment is carried out by conducting a written-based exam. Merdeka curriculum-based evaluation has several things that are broken down again, especially in the summative assessment section such as project and portfolio-based assessments, skill-based assessments and teacher and student reflection sheets. In this case, summative assessment with portfolio project assessment, skills, teacher and student reflection journals as well as independent and peer, has not been carried out properly and relevantly. This is perceived as a deficiency by teachers in the implementation of evaluations. The advantages present are that teachers are able to activate learning and see the success of student learning in depth and are able to design teaching materials according to student needs. Based on the qualitative questionnaire that accompanied this study, the implementation of the evaluation of Arabic language learning based on the independent curriculum was at 60% of the implementation stages.